(3TQM GdUOhQ HGdUdGI hGdSdGe Ydi GdfGUQ GdefUhQs - (3Gdedhj GdeLjQj GdTGaYqj GdCRgQj, CHh GdYHGS, TgGH GdOjf, CMeO Hf YHO GdaJGM Hf jhSa, J(B1181(3g`s
(3ChdgG (B:s
(3jbhd CMeO Hf YHO GdaJGM GdeLjQj GdedhjGdMeO ddg GdQMje GdZaGQhHYO agPg UdhGJ Ydi GdfHj Udi Gddg Ydjg hSde LdjdI GdebOGQs
(3BNQgG (B:s
(3CMOfG jcKQ GdUdGI Ydjg MJi jUjQ eSCdI YeG jTcd Ydjg ef CeQ Ojfg aj GddjdI hGdjhes
(3aj BNQg COYjI hahGFO aj GdJUha dYHO GdZfj GdfGHdSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 152s
(3eYLe GdeDdajf(B: 1 / 172s
(3EjVGM Gdecfhf(B: 2 / 45s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs